Réécrire le symbolique: entre l'ironie et l'engagement politique L'Euguélionne de Louky Bersianik - Krzykawski, Michał (Romanica Silesiana)
The analysis of irony in Louky Bersianik’s “The Euguelionne” as one of the major feminist strategies to present the voice of the ’ex-centric’ – is central in this article. The author shows that although parody is caught up in the dialectics of transgression, and thus based on the inherent presence of the parodied text, it is also involved in the oppressing discourse and thanks to its deconstructive power has the potential to de-naturalize what has never been natural. Key words: feminism; parody; irony; satire; discursive strategies; identity; phallogocentrism; deconstruction